2018
DOI: 10.3389/fpls.2018.00001
|View full text |Cite
|
Sign up to set email alerts
|

Metarhizium brunneum (Ascomycota; Hypocreales) Treatments Targeting Olive Fly in the Soil for Sustainable Crop Production

Abstract: Soil treatments with Metarhizium brunneum EAMa 01/58-Su strain conducted in both Northern and Southern Spain reduced the olive fly (Bactrocera oleae) population density emerging from the soil during spring up to 70% in treated plots compared with controls. A model to determine the influence of rainfall on the conidial wash into different soil types was developed, with most of the conidia retained at the first 5 cm, regardless of soil type, with relative percentages of conidia recovered ranging between 56 and 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
510
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 479 publications
(530 citation statements)
references
References 38 publications
19
510
0
Order By: Relevance
“…On the other hand, we calculated the LC 50 of H. didymator inoculated with the EAMa 01/58‐Su strain, which was of 1.85 × 10 6 conidia ml −1 . Although our results are consistent with those obtained for this strain and other parasitoids, it is shown that the susceptibility of H. didymator to EAMa 01/58‐Su is higher than those evidenced by different insect pests . This result is of great importance to develop a suitable strategy for biological control as it allows to compare the susceptibility of the parasitoid with other insects.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…On the other hand, we calculated the LC 50 of H. didymator inoculated with the EAMa 01/58‐Su strain, which was of 1.85 × 10 6 conidia ml −1 . Although our results are consistent with those obtained for this strain and other parasitoids, it is shown that the susceptibility of H. didymator to EAMa 01/58‐Su is higher than those evidenced by different insect pests . This result is of great importance to develop a suitable strategy for biological control as it allows to compare the susceptibility of the parasitoid with other insects.…”
Section: Discussionsupporting
confidence: 90%
“…(Hymenoptera: Braconidae), were susceptible to B. bassiana and M. anisopliae . Similarly, our previous work with the same strain (EAMa 01/58‐Su) and the same concentration (10 8 conidia ml −1 ) that we used in the present article, showed that the fungus caused a mortality of 21% on adults of the cosmopolitan parasitoid Psyttalia concolor Szepliget (Hymenoptera: Braconidae) …”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations